Effect of Content Marketing and Celebrity Endorser on Purchasing Decisions with Brand Trust as an Intervening Variable - Budi Susilo, Tri Achmad; Rahma, Nida Adenia; Wilujeng, Ita Prihatining; Siswanto, Ely (JURNAL MANAJEMEN MOTIVASI, 2025)
This study aims to analyze the influence of content marketing and celebrity endorsers on purchase decisions with brand trust as a mediating variable among Tomoro Coffee consumers at the Sidoarjo branch through the TikTok platform. A quantitative approach was used with purposive sampling involving 200 respondents from Generation Z who are active TikTok users and have purchased Tomoro Coffee. Data were analyzed using SmartPLS 4. The results show that content m|arketing and celebrity endorsers have a positive and significant effect on brand trust. However,both variables negatively and significantly affect purchase decisions when examined directly. Meanwhile, brand trust has a positive and significant impact on purchase decisions and is proven to mediate influence of content marketing and celebrity endorsers on purchase decisions. The findings highlight the importance of building strong brand trust through appropriate content strategies and celebrity endorsement to enhance consumer purchasing effectiveness